MENGUKUR KINERJA REFORMASI HUKUM BIROKRASI PENGADAAN BARANG DAN JASA PEMERINTAH - Jawade Hafidz (Faculty of Law, Universitas Diponegoro, 2014)
Law which regulates public procurement of goods and services are becoming increasingly important in developing countries such as Indonesia, especially in monitoring performance and for transparency. Regulation and supervision in public procurement of goods and services is the power of government and the basis for bureaucratic reform in public procurement. Public procurement involving multiple parties require strict control to avoid deviations which can be detrimental to the country. Comprehension and understanding of the scope, activity events, parties involved, performance measures, as well as the application of principles and ethics which is implemented consistently in accordance with the regulations of the procurement of goods/services will accelerate bureaucratic reform efforts in Indonesia.